Pozaziemskie pochodzenie sztyletu Tutanchamona a odkrycia naukowe - Napierała, Mateusz (Folia Praehistorica Posnaniensia, 2025)
The aim of the article is to verify, using the example of Tutankhamun’s iron dagger, how easily incorrect information can be disseminated in mass culture. This artefact has been repeatedly subjected to physicochemical analyses, yielding increasingly more precise data. In this article I will present the most important results of these studies to show the current state of knowledge on this subject. An important part of the knowledge about this artefact are also the hypotheses related to determining its origin. Outlining them will highlight the most important problems that still exist and dispel doubts and inconsistencies that often appear on the Internet. Implementation of the above assumptions will provide valuable information, contrasting it with catchy headlines appearing on the Internet.